Fitoremediasi Logam Kadmium (Cd) dari Asap Rokok Menggunakan Tanaman Puring (Codiaeum Variegatum) - Kurniawati L; Syamsidar HS; Kurnia Ramadani (Al-Kimia, 2016)
Environmental problems in Indonesia even in the world of growing. One of the factors causing the environmental problems with surging smoking habits in society that cause air pollution. One of the pollutants generated from cigarette smoke is a cadmium (Cd) metal. One of the efforts made in reducing pollutants in the air, especially Cd metals is phytoremediation method using plant croton (Codiaeum variegatum). This study aims to determine the ability of plants to absorb Cd metals croton. The method is performed by directly exposure at 3, 6 and 9 days. Instrument used in this study is an atomic absorption spectrophotometer (AAS). The results showed that the croton leaves absorb Cd metal with a maximum concentration of 1,065 mg/kg on days 9, so that it can be used as Cd metal phytoremediator